Haemodynamic Balance in Acute and Advanced Heart Failure: An Expert Perspective on the Role of Levosimendan - Piergiuseppe Agostoni; Dimitrios T Farmakis; Jose M García-Pinilla; Veli-Pekka Harjola; Kristjan Karason; Dirk von Lewinski; John Parissis; Piero Pollesello; Gerhard Pölzl; Alejandro Recio-Mayoral; Alexander Reinecke; Patrik Yerly; et al. (Cardiac Failure Review, 2019)
Acute and advanced heart failure are associated with substantial adverse short- and longer-term prognosis. Both conditions necessitate complex treatment choices to restore haemodynamic stability and organ perfusion, relieve congestion, improve symptoms and allow the patient to leave the hospital and achieve an adequate quality of life. Among the available intravenous vasoactive therapies, inotropes constitute an option when an increase in cardiac contractility is needed to reverse a low output state. Within the inotrope category, levosimendan is well suited to the needs of both sets of patients since, in contrast to conventional adrenergic inotropes, it has not been linked in clinical trials or wider clinical usage with increased mortality risk and retains its efficacy in the presence of beta-adrenergic receptor blockade; it is further believed to possess beneficial renal effects. The overall haemodynamic profile and clinical tolerability of levosimendan, combined with its extended duration of action, have encouraged its intermittent use in patients with advanced heart failure. This paper summarises the key messages derived from a series of 12 tutorials held at the Heart Failure 2019 congress organised in Athens, Greece, by the Heart Failure Association of the European Society of Cardiology.